Physicochemical and Functional Properties of Flour from the Wild Edible Mushroom Termitomyces heimii Natarajan Harvested in Côte d’Ivoire - Edmond Ahipo Due; Koffi Djary Michel; Yolande Dogore Digbeu (Turkish Journal of Agriculture: Food Science and Technology, 2016)
In Sub-Saharan Africa, especially, in Côte d’Ivoire, the wild edible mushroom Termitomyces heimii Natarajan is the most prized and widely consumed for different reasons such as taste, flavour, attractiveness, uses as substitutes for meat or fish and medicinal values. The present study was aimed at evaluating the proximate composition and functional properties of T. heimii flour for further food products formulation. Fresh mushroom T. heimii were obtained from the market of Aboisso (5° 28′ 06″ N and3° 12′ 25″ W) in Côte d’Ivoire. The fresh mushrooms were dried and ground to obtain the crude flour. Chemical composition and functional properties were investigated using standard methods. The chemical composition revealed that it contains crude protein about 23.75%, crude fat 3.58%, moisture 11.59 %, ash 7.40%, total carbohydrate 54.70% and energy value of 345.90 kcal/ 100 g. These results suggest that T. heimii can be used in human diet to prevent undernourishment due to protein. Furthermore, the low fat content suggest that it would be an ideal food for obese persons and useful in preventing hypertension and hypercholesterolemia. The functional properties showed that it has high bulk density and water absorption capacity with values of 0.737 g/mL and 315.15 ± 45.74% respectively. This flour exhibited also good foaming properties. All these characteristics make it suitable as good thickeners in food products, useful in foods such as bakery products which require hydration and attractive for products like cakes or whipping topping where foaming is important. The mushroom T. heimii could be utilized for making some low-fat foodstuffs and snacks with considerable protein content. The mushroom flour shows good functional characteristics for use in many food industries.